Desenvolvimento e validação de métodos cromatográficos para avaliação de interferon-alfa 2a em formulações farmacêuticas - Silva, Lucélia Magalhães da (2009)
The interferon is a cytokine with antiviral, antiproliferative, and immunomodulatory properties. It is a protein synthesized by cells in response to viral infection, producing successive biochemistry alterations. The chromatographic methods for evaluation of recombinant interferon-alfa 2a (rhIFN-α2a) in pharmaceutical products were validated in the present work. The reversed-phase liquid chromatography method (RP-LC) was developed and validated using a Jupiter C4 column (250 mm x 4.6 mm), maintained at ambient temperature (25°C). The mobile phase A consisted of 0.1% trifluoroacetic acid (TFA) and mobile phase B consisted of 0.1% TFA in acetonitrile, run in gradient: 0.01 1 min, 38% of B; 1 5 min, 38 43% of B; 5.01 20 min, 43 45% of B; 20.01 30 min, 45 48% of B; 30.01 40 min linear back to 38% of B and 40 42 min, 38% of B. The flow rate used was 1 mL/min with detection at 214 nm. The chromatographic separation was obtained within 42 min and it was linear in the concentration range of 0.5 50 MIU/mL (r2=0.9999). The size exclusion method was developed and validated using a BioSep-SEC-S 2000 (300 mm x 7.8 mm), maintained at ambient temperature (25°C). The mobile phase consisted of 1mM potassium phosphate monobasic, 8mM sodium phosphate dibasic and 200mM sodium chloride buffer, pH 7.4, run at a gradient flow rate: 0.01 20 min, 0.5 mL/min; 20 25 min, 0.5 1.7 mL/min; 25 35 min, 1.7 mL/min; 35 38 min, 1.7 0.5 mL/min; 38 40 min, 0.5 mL/min. The method was linear in the concentration range of 0.5 - 50 MIU/mL (r2=0.9996). The procedures were validated by the parameters of specificity, linearity, precision, accuracy, robustness, limit of quantitation and limit of detection. The methods were applied for the evaluation of the rhIFN-α2a in pharmaceutical products, contributing for the establishment of alternatives which improve the quality control, assuring the safety and therapeutic efficacy of the biological product.